Opazovanje pojavov prekinitev in obtoževanj na primeru pogovornih oddaj Trenja in Pod žarometom - Beguš, Ines (Annales. Series historia et sociologia, 2008)
Public communication is a process taking place among speakers in a public sphere in front of a wider audience. Speakers try to conduct themselves in an objective and neutral manner, yet do not always succeed. Disagreements between speakers lead to emotional reactions, perceivable in the form of verbal aggression and rude interruptions, termed accusations and interruptions in the present paper. Both processes are thought to represent emotional responses arising from disagreements between the two speakers in a debate and can arise separately, combined or reciprocally as cause and consequence. Most important in panel discussions is the role of the moderator, who must keep a neutral stance throughout the entire debate, yet can influence the speakers to act in a verbally aggressive manner by posing provocative questions or with ambiguous quotations. Interruptions and accusations often appear simultaneously in the television broadcasts Trenja and Pod žarometom as reactions to an assertion on the part of the other speaker. In fact, often the moderators provoke such happening, by the manner they moderate the discussion. The analysis of talk-shows has shown, that verbally aggressive expression represents a problem to those public speakers, who try to preserve their rule of conduct, and a positive factor for the creators of panel discussions as their main interest is to gain as many direct answers to their questions they possibly can
Keywords: javne razprave; konfliktnost; medosebna komunikacija; pogovorne oddaje; televizijske oddaje